Successful management of hepatitis B and C coinfection: a case report - Freidenson-Bejar, Jeffrey (2024)
We report the case of a patient with chronic hepatitis B and C managed with direct-acting antivirals in an outpatient setting. Chronic hepatitis B was first treated with entecavir before initiating treatment for chronic hepatitis C. The patient achieved viral suppression for hepatitis B and sustained virological response for hepatitis C. As direct-acting antivirals become more available, healthcare practitioners should be familiar with managing patients with chronic coinfection.